Geography and Religious Knowledge in the Medieval World - Mauntel, Christoph (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2021)
In the premodern world, geographical knowledge was influenced by religious ideas and beliefs. This volume brings together case studies from the Latin-Christian as well as the Arabic-Islamic geographic tradition. In a comparative perspective the contributions ask, how religious knowledge influenced the way the world and its geography were perceived and described.